Sediment resuspension in Cold Density Currents cascading down lateral slopes of Lake Geneva - Mettra, François; Reiss, Rafael Sebastian; Lemmin, Ulrich; Doda, Tomy; Blanckaert, Koen; Bouffard, Damien; Barry, David Andrew (Frontiers in Water, 2026)
Cold-water Density Currents (CDCs) resulting from winter differential cooling and flowing down lateral slopes of a lake (winter cascading) can entrain sediment and contribute to cross-shore transport to its deeper layers. Field investigations along Lake Geneva’s northern shore reveal how CDCs induce sediment resuspension. Acoustic backscattering demonstrated that sediment resuspension is absent at 10-m depth on the steep slope (~30°) just beyond the edge of the shallow coastal shelf where CDCs were initiated but occurred intermittently at 30-m depth where the flow reached higher velocities (slope reduced to ~4.5°). This suggests that CDCs resuspend sediment on the sloping bed (but not on the shelf edge) and potentially transport it to deeper layers, causing sediment focusing (i.e., thicker sedimentation in deeper zones). During CDCs, resuspension occurs in short bursts, often at the head of CDC impulses, creating plumes that can extend to ~1.5 m above the lakebed. Velocity profiles near the bed were well fitted by a logarithmic profile, from which the Shields parameter was determined and compared to the critical Shields stress. However, the strong time-variability of the downslope velocity prevents computation of a representative Shields parameter needed to determine sediment resuspension. The CDC velocity at 1 m above the bed (above ~9 cm s−1) correlated well with high backscattering echo level (indicating sediment resuspension) and was a better predictor for resuspension than the Shields parameter. Since CDCs were found to occur ~25% of the days in winter, CDC-induced resuspension potentially affects lake ecosystem dynamics.